Illustrating Power Relations through Symbolism in The Prisoner Who Wore Glasses - Larasati, Dyah Ayu (Celt: A Journal of Culture, English Language Teaching & Literature, 2023)
Symbolism is a powerful tool employed by authors to convey ideas and thoughts through the use of symbols and signs, imbuing everyday objects with deeper meanings in their works of literature. In addition, symbolism can have political implications, as it can represent political institutions, hierarchies, movements, beliefs, or ideologies, through objects, people, words, performances, or gestures. Through a content analysis approach, this research examines the symbolism used in  The Prisoner Who Wore Glasses and how everyday objects are utilized to depict power relations. The symbols analyzed in this research are glasses, fertilizer, and tobacco. Glasses were found to represent Brille’s vulnerability/intellect. Fertilizer symbolizes Warder Hannetjie’s weakness, and tobacco symbolizes authority. By analyzing the symbols portrayed in literary works, especially writings that have a political connotation to them, it goes to show that sometimes the objects portrayed in literature are not just depicted for creative intentions, but also for critical depth.